770 Risk Factors Associated with Anemia and Nutritional Status in Infants. (October 2012) - Cazan, C; Neamtu, ML; Dobrota, L
Abstract : Background: Growth assessment is an integral part of infants health. An understanding of anemia risk factors is essential to identify the groups that are more vulnerable. The Aim: of the study was to identify the risk factors for malnutrition in the vulnerable age group of 6 to 12 months and to evaluate possible related risk factors with anemia. Methods: The cross-sectional study which evaluated 206 infants aged between 6–12 months who attended the Pediatric Clinic during the years 2010–2011 for inadequate growth. Mothers were interviewed to collect informations regarding socioeconomic status and nutrition practices. Nutritional status was evaluated by anthropometric measurements using growth charts. Anemia was diagnosed if hemoglobin was ≤11 g/dL. Results: Mild and moderate anemia was characterised by hemoglobin levels below 11.0 and 9.5 g/dL. Rates for mild and moderate anemia were 38.6% and 11.9%. The highest anemia prevalence was found at 6 to 8 months of age. The risk factors for anemia were: urban residence (p=0 . 004), fever in the past 5–7 days (p<0 . 001) and age at 6–8 months (p=0 . 024), socioeconomic level and nutrition practices. Infants who were exclusively breastfed for 6 months showed lower prevalence of anemia compared to their mixed feeding. According to weight and length for-age, 49% of the infants were at 25 th, 32% at 10 th, 9.2% at 5 th and there was a significant correlation between the duration of breastfeeding and nutritional status. Conclusions: Strategies to control infant anemia should include health promotion and nutritional education for families from all socioeconomic levels.